Health Services Research in Rehabilitation and Disability – The Time is Now - Graham, James E. (Arch Phys Med Rehabil, 2017)
Policy drives practice, and health services research (HSR) is at the intersection of policy, practice and patient outcomes. HSR specific to rehabilitation and disability is particularly needed. As rehabilitation researchers and providers, we are uniquely positioned to provide the evidence that guides reforms targeting rehabilitative care. We have the expertise to define the value of rehabilitation in a policy-relevant context. HSR is a powerful tool for providing this evidence. We need to continue building capacity for conducting rigorous, timely rehabilitation-related HSR. Fostering stakeholder engagement in these research efforts will ensure we maintain a patient-centered focus as we address the “Triple Aim” of better care, better health, and better value. In this Special Communication we discuss the role of rehabilitation researchers in HSR. We also provide information on current resources available in our field for conducting HSR and identify gaps for capacity-building and future research. Healthcare reforms are a reality, and through HSR we can give rehabilitation a strong voice during these transformative times.